Pengaruh Partisipasi Pengguna Dalam Pengembangan, Kemampuan Pengguna dan Dukungan Manajemen Puncak Terhadap Kinerja Sistem Informasi Akuntansi Pada Moment Coffee Semarang - Nurdhiana; Triani; Natasya Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study was to determine the factors that affect the performance of accounting information systems. The population and sample amounted to 30 respondents, saturated sample collection technique (census). Data analysis tools used multiple linear regression, tested classical assumptions, classical assumption tests and reliability tests. User participation has a positive effect on the performance of accounting information systems, user skills have no effect on the performance of accounting information systems, top management support has no effect on the performance of accounting information systems.